2017
DOI: 10.1097/bpo.0000000000000665
|View full text |Cite
|
Sign up to set email alerts
|

Delay in the Diagnosis of Stable Slipped Capital Femoral Epiphysis

Abstract: Level III-prognostic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 10 publications
0
33
0
3
Order By: Relevance
“…Green et al 7 evaluated the primary care system, which included the emergency department, urgent care setting and paediatricians, and found that in 102 patients, the average delay from their first visit with a primary care provider to the time of admission was 10.0 weeks. Hosseinzadeh et al 11 found in their series of 149 patients, that patients presenting to orthopaedic surgeons had a 0.4 week delay in a SCFE diagnosis compared with 13.4 weeks when the patient presented to non-orthopaedic providers. Similarly, Schur et al 10 reported that in their study of 481 patients, the time from first evaluation to diagnosis was significantly shorter for patients evaluated at an orthopaedic clinic (0 weeks) than patients evaluated by a primary care provider (four weeks) or at an emergency department (six weeks).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Green et al 7 evaluated the primary care system, which included the emergency department, urgent care setting and paediatricians, and found that in 102 patients, the average delay from their first visit with a primary care provider to the time of admission was 10.0 weeks. Hosseinzadeh et al 11 found in their series of 149 patients, that patients presenting to orthopaedic surgeons had a 0.4 week delay in a SCFE diagnosis compared with 13.4 weeks when the patient presented to non-orthopaedic providers. Similarly, Schur et al 10 reported that in their study of 481 patients, the time from first evaluation to diagnosis was significantly shorter for patients evaluated at an orthopaedic clinic (0 weeks) than patients evaluated by a primary care provider (four weeks) or at an emergency department (six weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Although the time from symptom onset to first physician visit was identified as a major contributor to the delay, this cannot be altered by clinicians. 11 However, healthcare providers can help decrease the time from the first visit to diagnosis. Several studies have reported on the impact that healthcare provider specialty has on delayed diagnosis of a SCFE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-orthopedics are more prone not to diagnose a slip during the first examination of the patient [29]. Physicians must be aware of the rare conditions of the hip that may cause a limp.…”
Section: Discussionmentioning
confidence: 99%
“…El envío al ortopedista pediatra debe efectuase tan pronto como se tenga la sospecha o se haya establecido el diagnóstico, pues el retraso en el tratamiento se asocia con mal pronóstico, debido al alto riesgo de osteonecrosis de la cabeza femoral. 19,13…”
Section: Intervención Del Especialistaunclassified